Alkali Hydrogen Peroxide (AHP) Pretreatment to Increase The Cellulose Content In Durian Peel Waste - Nur Makhmudi; Tri Utami Setyawati; Sani Sani; Aisyah Alifatul Zahidah Rohmah; Raka Selaksa Charisma Muchammad (Universitas Islam Raden Rahmat, Malang, 2026)
Indonesia is one of the largest producers of durian, generating substantial quantities of durian peel waste. Due to its high cellulose content, durian peel has strong potential as a lignocellulosic feedstock for reducing sugar and biofuel production. However, the presence of lignin and hemicellulose limits cellulose accessibility and inhibits hydrolysis. This study investigated Alkali Hydrogen Peroxide (AHP) pretreatment to enhance cellulose purity in durian peel waste. Pretreatment was carried out using H₂O₂ concentrations of 0.5–8.5% (w/v) with NaOH adjustment to pH 11–12 at 70°C for 3 h. The optimum condition was obtained at 8.5% H₂O₂, which increased cellulose content from 63.02% to 75.05%, reduced hemicellulose by 24.4%, and removed 99.5% of lignin. Scanning Electron Microscopy (SEM) analysis confirmed the formation of a rougher and more porous surface after pretreatment, indicating disruption of the lignocellulosic structure. Statistical analysis using ANOVA showed that H₂O₂ concentration significantly affected cellulose, hemicellulose, and lignin responses (p < 0.05). These results demonstrate that AHP pretreatment is highly effective in improving cellulose accessibility and provides a promising approach for converting durian peel waste into reducing sugars and other bio-based products.